Efektivitas Keberlakuan Peraturan Mahkamah Agung Nomor 1 Tahun 2016 Tentang Mediasi dalam Perkara Perceraian Pengadilan Agama Kelas 1A Palembang - Risma, Alifiah; Ifrohati (Journal of Sharia and Legal Science, 2024)
The purpose of this study is to examine the effectiveness of the implementation of the Supreme Court Regulation on Mediation in the Religious Court of Palembang City. A mediator is a judge or other party who has a mediator certificate as a neutral party who helps the parties in the dispute resolution process without using the method of deciding or forcing a settlement between the parties. However, this mediation is often unsuccessful in reconciling the parties, especially in divorce cases. This type of research is field research. The method used in this study is a qualitative method. The data sources used are primary data, namely the results of interviews, secondary data, namely those from books, journals, and others. The results of the study show that the mediation procedure in divorce cases at the Palembang Religious Court Based on Supreme Court Regulation Number 1 of 2016 has been implemented effectively, the mediator on duty already has a certificate. However, the parties who mediate in divorce cases at the Palembang Religious Court prioritize feelings over anything else, causing the mediation to fail. The factors that influence the success of mediation in divorce cases at the Class 1A Religious Court of Palembang are child factors, family factors, the role of the judge and the mediator.